(untitled) (Saúde Ética & Justiça, 2021)
The Covid-19 pandemic began at the end of 2019 and imposed significant challenges on the academic community. This research aimed to observe the landscape of clinical research involving Covid-19 and verify the scientific community’s engagement with the subject by comparing the number of projects on this specific illness to those on other more prevalent diseases. The official data released by ClinicalTrials.org were used. Covid-19 and the diseases considered major causes of death were researched in the named database using keywords between 01/01/2020 and 31/12/2021 and in the biennium before the pandemic (2018-2019), respectively. Data analysis showed the academic community’s commitment in all regions of the world, with a higher incidence of studies focused on Covid-19 than on other important diseases. Interventional and observational studies were quantitatively similar, both directed at adults and older adults of both sexes.